Terrorist attacks versus acts of illegal interference in civil aviation. Implications for the functioning of airport critical infrastructure - Siadkowski, Adrian (Przegląd Strategiczny, 2011)
What makes the attacks on aviation transport so attractive is the fact that the act of aggression aimed at means of transport has an impact not only on the craft and vehicles themselves, but also on the critical infrastructure, the passengers, the crew and is followed by the wide interest of media due to the spectacular side of the event. The distinction between a terrorist act and illegal interference act may raise the suspicion of various implications for the functioning of critical infrastructure of an airport, first and foremost the designing of security and protection systems. As it may seem, providing safety will be adequate to anti-terrorist activities whereas the protection of civil aviation will be assigned to the prevention of acts of illegal interference. Such a course of thinking would imply the division or at least conduction of parallel actions. In practice, those areas overlap one another and widen the range of possible actions or use of certain instruments, for example legal ones. Also, the differences in prevention systems against terrorist acts and illegal interference acts are only slight.